The Questionable Case for Using Auctions to Select Lead Counsel - Lucian Arye Bebchuk (Washington University Law Quarterly, 2002)
This Article analyzes the shortcomings of using auctions for selecting lead counsel in class action cases. In contrast to what proponents of auctions suggest, the outcome of an auction is likely to diverge considerably from what an informed principal would have chosen. In particular, auctions push the percentage of recovery paid to counsel to the lowest level at which law firms would be willing to take the case. Because of the need to provide counsel with incentives to invest effort and resources, however, the class might well be better served by a higher percentage than this minimum level, and auctions might push fees to levels that are too low. The analyzed problems are ones that arise also in those types of cases for which the use of auctions should be considered according to the recent recommendations of a Task Force report.
Keywords: Class actions (Civil procedure); Securities; Letting of contracts; Class counsel – Auctions; Court appointed counsel